Reconfigurable Metamaterial Structure at Millimeter Wave Frequency Range - B. A. F. Esmail; H. A. Majid; Z. Z. Abidin; S. H. Dahlan; M. K. A. Rahim (Institute of Advanced Engineering and Science, 2017)
In this paper, reconfigurable metamaterial structure at millimeter wave frequency range was designed and simulated for a future fifth generation (5G) mobile-phone beam switching applications. The new proposed structure was composed of a bridge-shaped resonator (BSR) in the front face and strip line at the back face of the unit cell which operates at 28 GHz. First, non-reconfigurable low loss BSR unit cell was designed and subsequently, the reconfigurability was achieved using four switches formed in the gaps of the structure. The proposed structure achieves the lowest loss and almost full transmission among its counterparts by -0.06 dB (0.99 in linear scale). To demonstrate the reconfigurability of the metamaterial, the reflection and transmission coefficients and real parts of the effective refractive index at each reconfigured frequency were studied and investigated. Simulation results showed that a high transmission and reflection peaks occur at each resonance frequency according to change the state of the switches.